PENGARUH KEBIJAKAN KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PROYEK KONSTRUKSI PADA PT. MULTI JAYA CONCEPTS DI SAMARINDA - HS, Syamsurahman (EKONOMIA, 2014)
Safety and health maintenance programs, including one in the company, The implementation of occupational safety and health program for employees is essential as it aims to create a system of safety and occupational health management, involving elements, labor, conditions, communication and integrated working environment in order to reduce accidents. This study aims to analyze the influence of occupational health and safety policies on employee performance in the construction of PT. Multi Jaya Concepts disamarinda, formulation of the problem in this research is